Relationships between the antral follicle count, steroidogenesis, and secretion of follicle-stimulating hormone and anti-Müllerian hormone during follicular growth in cattle - Kenichiro Sakaguchi; Yojiro Yanagawa; Koji Yoshioka; Tomoko Suda; Seiji Katagiri; Masashi Nagano (BMC, 2019)
Abstract Background The antral follicle count (AFC) in mammalian ovaries positively correlates with female fertility. To clarify the causes of differences in fertility between low and high AFC cows, we investigated follicular growth dynamics and hormone concentrations in plasma, follicular fluid, and in vitro growth (IVG) media at different stages of follicular growth. Methods Seven cows were divided into high AFC (n = 4, > 30 follicles) and low AFC (n = 3, < 30 follicles) groups based on the peak AFC detected by ultrasonography. These cows were subjected to estrous synchronization, daily ovarian ultrasonography, and blood collection. Their follicular fluid was collected from dominant follicles at different stages (selection, luteal, and ovulatory phases). In another experiment, we cultured oocyte-cumulus-granulosa cell complexes collected from early antral follicles (< 1 mm) for 12 days. Estradiol-17β (E2), testosterone (T), progesterone (P4), and anti-Müllerian hormone (AMH) concentrations in follicular fluids and plasma were measured. Plasma follicle-stimulating hormone (FSH) concentrations were examined. E2, P4, and AMH concentrations were also measured in IVG media. Results The numbers of small (< 4 mm) and intermediate (4-8 mm) follicles were larger in the high AFC group than in the low AFC group (P < 0.05). The number of intermediate follicles was stable in the low AFC group, indicating consistent development. However, the number of these follicles fluctuated in the high AFC group. Plasma FSH concentrations were higher, whereas E2 and T concentrations were lower in the low AFC group (P < 0.05). E2 concentrations and the E2/P4 ratio in ovulatory follicles and IVG media on day 8 were higher in the high AFC group (P < 0.05). AMH concentrations in plasma and IVG media (P < 0.01) were higher in the high AFC group. Conclusions The weaker response to FSH of granulosa cells caused low E2 production in the low AFC group, resulting in high FSH concentrations and the consistent development of intermediate follicles. Conversely, higher E2 concentrations suppressed FSH secretion in the high AFC group. Granulosa cells in the high AFC group had the ability to produce more AMH than those in the low AFC group throughout IVG culture.